Pengembangan Praktik Pelayanan Prima dalam Kebijakan Pemerintah (JIANA ( Jurnal Ilmu Administrasi Negara ), 2009)
In the practical Public Administration as an art is more develop than as a science ofdichotomy of anminstration and poliitics in the Old Public Administration paradigm also in NewPublic Management paradigm, with the transformation of orientation to efficiency and effective-ness of economy as the spirit of the entrepreneurship through the idea of Reinventing Govern-ment. The turning point of Public Administration as Public Administration Sicence got its powerfulcharacter through Public New Service hat seen the locus and the focus on the public services tothe public as the owner of the state sovereignty. This symton picturisqued and expressed thedemocratic principal in the public policy process. To gain a model for premium service, tne need ofknowing the real-time condition of empowering and intervention of technology or new method willappear integrated and synergic management between effectiveness and efficiency.